Análise da estrutura genética populacional de duas espécies de Characiformes (Pygocentrus nattereri e Potamorhina latior) na região da bacia do Rio Madeira, Rondônia - Marín, Jorge Mori [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The order Characiformes gathers approximately 1,670 freshwater species, of which at least 1,300 occur in Brazil. To date relatively few genetic studies have been conducted with species of this group, particularly in the Amazon. An important question for the moment is whether there is some isolation between local populations separated by rapids or fast in the Amazon, given the hydroelectric potential estimated for these environments. Accordingly, in this study, conducted under the Conservation Program Ichthyofauna of Santo Antônio Energia, were evaluated two local populations of two species: Pygocentrus nattereri and Potamorhina latior. We employ sequences of the control region (D-loop) of the mitochondrial DNA, the higher rate of this gene mutation present in relation to other genes. The samples were taken upstream and downstream of the old waterfall Teotônio to test the hypothesis that this waterfall served as a barrier for these species. Were examined 54 specimens of P. nattereri (25 upstream and 29 downstream) and 45 of P. latior (25 upstream and 20 downstream). The results showed that the amount of specimens of P. nattereri have greater genetic variability (Haplotypes = 5, Hd = 0607, π = 0.00105) that the downstream (Haplotypes = 2, Hd = 0379, π = 0.00046). In the case of P. latior, these values were similar both upstream (Haplotypes = 23, Hd = 0993, π = 0.01232) and downstream (Haplotypes = 17, Hd = 0.984, π = 0.01865). Both species have shared haplotypes in the two localities. The genetic divergence between the localities of P. nattereri (0.1%) was lower than in P. latior (1.9%). The analysis of molecular variance revealed significant differences between the localities of P. nattereri (Φst = 0.11448, P = 0.018) and P. latior (Φst = 0.16408, P = 0.000). The results suggest that a possible population structure existed between the two localities sampled both by differences in genetic variability as well as by allelic ...

A ordem Characiformes reúne aproximadamente 1.670 espécies de água doce, das quais pelo menos 1.300 ocorrem no Brasil. Até o momento relativamente poucos estudos genéticos foram realizados com espécies desse grupo, particularmente na Amazônia. Uma questão importante para o momento atual é saber se há algum isolamento entre populações locais separadas por corredeiras ou rápidos na Amazônia, dado o potencial hidrelétrico estimado para esses ambientes. Nesse sentido, no presente estudo, conduzido no âmbito do Programa de Conservação da Ictiofauna da Santo Antônio Energia, foram avaliadas duas populações locais de duas espécies: Pygocentrus nattereri e Potamorhina latior. Empregamos sequências da região controle (D-loop) do DNA mitocondrial, pela maior taxa de mutação que esse gene apresenta em relação aos demais genes. As amostras foram tomadas a montante e a jusante da antiga cachoeira de Teotônio visando testar a hipótese de que essa cachoeira servia de barreira para essas espécies. Foram analisados 54 espécimes de P. nattereri (25 montante e 29 jusante) e 45 de P. latior (25 montante e 20 jusante). Os resultados mostraram que os espécimes da montante de P. nattereri apresentam maior variabilidade genética (haplótipos = 5, Hd = 0,607, π = 0,00105) que os da jusante (haplótipos = 2, Hd = 0,379, π = 0,00046), No caso de P. latior, esses valores foram similares tanto a montante (haplótipos = 23, Hd = 0,993, π = 0,01232) como a jusante (haplótipos = 17, Hd = 0,984, π = 0,01865). Ambas as espécies apresentaram haplótipos compartilhados nas duas localidades. A divergência genética entre as localidades de P. nattereri (0,1%) foi menor que em P. latior (1,9%). A análise de variância molecular revelou diferenças significativas entre as localidades de P. nattereri (Φst = 0,11448, P = 0,018) e P. latior (Φst = 0,16408, P = 0,000). Os resultados sugerem que entre as duas localidades amostradas existia uma ...
Keywords: Ecologia; Zoologia; Genetica de populações; Characideo; Populations genetics